The Ego-Defensive Role of Legitimacy: How Threat-Based Justifications Protect the Self-Esteem of Discriminators - Pereira, Cícero Roberto (2018)
This article analyzes the ego-defensive role played by legitimation, by examining the hypothesis that threat-based justifications attenuate the negative effect on an individual’s self-esteem caused by his or her becoming aware of his or her own discriminatory behavior. Across three studies (including a pilot experiment), participants who were led to believe that they had acted in a discriminatory way experienced a decrease in their self-esteem. In Study 1 (N = 116), this effect was nullified when discrimination was justified by either symbolic or realistic threat perceptions. Study 2 (N = 250) replicated this pattern of results and went further by showing that discrimination affects self-esteem only in more egalitarian individuals, whereas for those less egalitarian, it affects their social image. According to the ego defensive role of legitimation, a meta-analytical integration of the results confirmed that the influence of discrimination in depressing self-esteem is moderated by threatbased justifications.